Tillage and Mulching in Relation to Soil Moisture Storage and Maize Yield in Foothill Region - Sanjay Arora; M.S. Hadda; Rajan Bhatt (Journal of Soil and Water Conservation, 2022)
To evaluate tillage and mulching practices for soil moisture conservation and productivity of rainfed maize, field experiments were conducted during two years in rainfed foothill region of North-west India. It was observed that with shallow tillage, deep tillage and ridge and furrow sowing treatment, soil moisture storage increased to the tune of 2.25, 4.01 and 10.77 per cent at 60 days after sowing, over farmers’ practice. The application of mulch as fully covered plot resulted in 48.4, 61 and 138 per cent higher soil moisture content at 40, 60 and 80 days after sowing, respectively. Fully covered plots had 156 per cent higher dry matter yield of maize compared to unmulched plots. There was 10.6 per cent increase in maize grain yield in ridge and furrow sowing over the farmers’ practice. Mulch spread on the whole plot increased the grain and straw yield of maize by 58.6 and 35.0 per cent as compared to unmulched control. Grain and straw yield in partially covered and strip application of mulch was significantly higher by30.0 and 28.3 % and 31.4 and 25.3 % respectively than in no-mulching treatment.